Computational Evaluation of Selectivity of Inhibition of Muscarinic Receptors M1-M4 - Mikurova, A.V.; Skvortsov, V.S.; Raevsky, O.A. (Biomedical Chemistry: Research and Methods, 2018)
A set of models for preliminary estimation of the inhibition constant values of potential ligands for the 4 acetylcholine muscarinic receptors M1-M4 was developed. The study uses an information about three-dimensional structure of human M1, M2 and M4 receptors, as well as the M3 receptor model, constructed by homology based on the structure of the rat M3 receptor. The Ki values for 42 compounds were obtained from the sources. Modeling of “protein-ligand” complexes was performed using molecular docking and molecular dynamics procedures. The component energy characteristics of the complexes were calculated from data obtained from simulation of molecular dynamics by the MM-PBSA/MM-GBSA methods. These characteristics were used as independent variables to construct the linear regression equations for pKi value predicting. The equations obtained for each receptors allow us to predict pKi with an average accuracy of 0.65 logarithmic units.